The Employee Engagement’s Impact on Productivity and Motivation in the Private higher education Sector in Oman - AlGhunaimi, Hisham; AlGhenaimi, Said (Journal of Ecohumanism, 2024)
Employee engagement in the workplace implies that employees are committed to their respective organizational vision, mission, and goals, thereby becoming more engaged, and motivated to contribute to organizational success. Similarly, engaged professional staff in Oman’s higher education sector experience job satisfaction, involvement, commitment, and empowerment, thereby enhancing education quality. Employee engagement has gained significant attention from scholars and practitioners due to its positive impact on personal and organizational well-being. Thus, this study aims to explore the effect of employee engagement on productivity and motivation in Oman’s private higher education sector and determine the success factors for organizations in maintaining employee engagement. The literature review reveals that the working environment, leadership style, and creative work approach tend to influence employee engagement in Oman’s private higher education sector. Therefore, secondary findings reveal the impact of different motivations and productivity on employee engagement through social exchange theory.